Urban development in India - Bhattacharya, B. (New Delhi, 1979)
'Urban Development in India since Pre historic Times' is the first attempt of its kind, giving facts about urbanization in the country that began almost for tyfive centuries ago. The book focuses, for the first time, on the underlying forces that contributed to the unchecked growth of towns and cities over centuries, revealing further the situation under which urban life in India had continued almost uninterrapted through a space of four and a half millennia. The book makes it palpably clear that, most of the great cities and towns today, towering above others and glowing in their respective accomplishments, have had their locations determined long ago and their survival through all situations indicates the soundness of their geographical settings. It brings to light the changes in the major axis of urban development and compares the present urban position with the other countries of world.
Keywords: Urbanization